2000
DOI: 10.1002/chin.200024090
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of 5‐Fluoro Salicylic Acid.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…High application costs of vat dyes have been studied by Sharma [69] with a view to reducing amounts of sodium hydrosulphite. Unpublished studies in this field have revealed the tendency for fibre tendering even in enclosed machines, unless sodium hydrosulphite concentration is maintained at a fairly high level.…”
Section: Cellulosic Fibres (A) Vat Dyesmentioning
confidence: 99%
“…High application costs of vat dyes have been studied by Sharma [69] with a view to reducing amounts of sodium hydrosulphite. Unpublished studies in this field have revealed the tendency for fibre tendering even in enclosed machines, unless sodium hydrosulphite concentration is maintained at a fairly high level.…”
Section: Cellulosic Fibres (A) Vat Dyesmentioning
confidence: 99%